Fluid dynamics of cricket ball swing - Scobie, J. A.; Pickering, S. G.; Almond, D. P.; Lock, G. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
Swing describes the lateral deviation of a cricket ball in its trajectory towards the batsman. Conventional swing is effective with a new, or well-preserved, ball, and the fluid dynamics governing this phenomenon was first explained in 1957. In 2012, many test-match fast bowlers are able to swing, at high speed, an older ball in the reverse direction. This reverse swing of a ball aged under match conditions has never been explained fully. A cricket ball is asymmetric with six seams of 80-90 encircling stitches, protruding approximately 1 mm proud of the surface. Both conventional and reverse swings are a consequence of asymmetrical flow separation leading to a skewed wake and a net pressure force on the ball perpendicular to the flight trajectory. Here, experimental evidence is presented for the first time showing that the formation of a laminar separation bubble is the prominent flow feature creating the flow asymmetry for reverse swing. A new flow visualisation technique to capture the fluid dynamics of boundary-layer separation using an infrared camera is also introduced here.